A test of the extended intergroup contact hypothesis: the mediating role of intergroup anxiety, perceived ingroup and outgroup norms, and inclusion of the outgroup in the self. - Turner, R; Hewstone, M; Voci, A; Vonofakou, C (2008)
S. C. Wright, A. Aron, T. McLaughlin-Volpe, and S. A. Ropp (1997) proposed that the benefits associated with cross-group friendship might also stem from vicarious experiences of friendship. Extended contact was proposed to reduce prejudice by reducing intergroup anxiety, by generating perceptions of positive ingroup and outgroup norms regarding the other group, and through inclusion of the outgroup in the self. This article documents the first test of Wright et al.'s model, which used structural equation modeling among two independent samples in the context of South Asian-White relations in the United Kingdom. Supporting the model, all four variables mediated the relationship between extended contact and outgroup attitude, controlling for the effect of direct contact. A number of alternative models were ruled out, indicating that the four mediators operate concurrently rather than predicting one another.